Analisis Kecepatan Routing Discovery Untuk Routing Protocol AODV, OLSR, Dan ZRP Pada Mobile Ad Hoc Network - Tulus Rahayu; Ery Syafrianti; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Ad hoc network is wireless network without a consistent node infrastructure. Every node could be used as a router to track another node in a network. Ad hoc could use several routing protocols. AODV, OLSR, and ZRP are among of them that are efficient for Ad Hoc network within each of their own type of routing protocol. Every routing protocol has different ability and various speed in order to track routing path in a network. The aim of this research is to determine Routing Discovery time for routing protocol AODV, OLSR, and ZRP in mobile ad hoc network (MANET). The research used the scenario where node's position is random within determined area. The results show that the routing discovery time for protocol AODV, OLSR, and ZRP are 0.035811829 seconds, 5.817611777 seconds and 1.052782493 seconds, respectively. Thus, AODV routing protocol has faster routing discovery time than the routing protocol OLSR and ZRP. Keywords : Ad Hoc Network, routing protocol, routing discovery, AODV, OLSR, ZRP.